In silico prediction of interactions and molecular dynamics simulation analysis of Mpro of Severe Acute Respiratory Syndrome caused by novel coronavirus 2 with the FDA-approved nonprotein antiviral drugs - Subramaniam Sivakumar, Sugumar Mohanasundaram, Narasimhan Rangarajan, Venkatesan Sampath, Maderi Velayutham Dass Prakash (Journal of Applied Pharmaceutical Science, 2022)
In the current scenario of the severe acute respiratory syndrome caused by novel coronavirus 2 (SARS-CoV-2) pandemic, the repurposing of the Food and Drug Administration (FDA)-approved antiviral drugs for the possibility of treating SARS-CoV-2 is an unavoidable scientific method. It further exemplifies the physical interactions between the target protein and the chosen drugs. In this study, the main protease (Mpro) structure of SARS-CoV-2 Protein Data Bank ID: 7BUY with 42 FDA-approved antiviral drugs was analyzed by molecular docking using PyRx-Vina, and the amino acids involved in docking are analyzed using Discovery Studio Visualizer. The protein–drug complex stability was analyzed by molecular dynamics simulation (MDS) using GROMACS. The results showed that ledipasvir showed the maximum binding affinity (−10.4 kcal/mol) with Mpro of SARS-CoV-2 followed by paritaprevir (−9.1 kcal/mol) and velpatasvir (−8.8 kcal/mol). These three compounds are found to have a significant number of interactions. Moreover, ledipasvir and velpatasvir showed similar interactions at GLU240, PRO241, ILE249, PRO293, and VAL202. MDS showed that the top ligands had formed stable complexes with Mpro. Molecular Mechanics Poisson–Boltzmann Surface Area calculation revealed thermodynamically stable binding energies of −195.370 ± 1.119 kJ/mol and −180.778 ± 0.868 kJ/mol for ledipasvir and velpatasvir, respectively. Paritaprevir showed stable binding energy of −75.679 ± 0.922 kJ/mol with Mpro of SARS-CoV-2.
Keywords: SARS-CoV-2, main protease, in silico, docking, repurposing, molecular dynamic simulation